Crystal structure of toxin HP0892 from Helicobacter pylori with two Zn(II) at 1.8 Å resolution. (15th April 2014) - Im, Hookang; Jang, Sun‐Bok; Pathak, Chinar; Yang, Yeon‐Jin; Yoon, Hye‐Jin; Yu, Tae‐Kyung; Suh, Jeong‐Yong; Lee, Bong‐Jin
Abstract: Antibiotic resistance and microorganism virulence have been consistently exhibited by bacteria and archaea, which survive in conditions of environmental stress through toxin–antitoxin (TA) systems. The HP0892–HP0893 TA system is one of the two known TA systems belonging to Helicobacter pylori . The antitoxin, HP0893, binds and inhibits the HP0892 toxin and regulates the transcription of the TA operon. Here, we present the crystal structure of the zinc‐bound HP0892 toxin at 1.8 Å resolution. Reorientation of residues at the mRNase active site was shown. The involved residues, namely E58A, H86A, and H58A/ H60A, were mutated and the binding affinity was monitored by ITC studies. Through the structural difference between the apo and the metal‐bound state, and using a homology modeling tool, the involvement of the metal ion in mRNase active site could be identified. The most catalytically important residue, His86, reorients itself to exhibit RNase activity. His47, Glu58, and His60 are involved in metal binding where Glu58 acts as a general base and His47 and His60 may also act as a general acid in enzymatic activity. Glu58 and Asp64 are involved in substrate binding and specific sequence recognition. Arg83 is involved in phosphate binding and stabilization of the transition state, and Phe90 is involved in base packing and substrate orientation. Abstract : PDB Code(s):4NRN